Effect of Ultrasonication Time on Structural, Morphological, and Functional Properties of Sugar Palm (Arenga pinnata Merr.) Flour Nanofibers - Tuty Anggraini; Kesuma Sayuti; Siti Sarah Humaira; Arif Rahman Zuhri; Rina Yenrina; Arif Rizkika Putra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Sugar palm (Arenga pinnata) flour has the potential to be developed into nanofibers for use as natural biopolymer materials. Ultrasonication is a promising method for modifying particle size and structural properties; however, the effects of different ultrasonication times on the characteristics of sugar palm flour nanofibers have not been fully explored. This study analysed the effect of different ultrasonication times on the physicochemical properties of sugar palm flour nanofibers produced with an ultrasonic probe homogeniser. A Completely Randomized Design (CRD) was applied with five ultrasonication times: 0 (control), 30, 60, 90, and 120 minutes, each with three replications. The evaluated parameters included morphology (SEM), particle size, crystallinity (XRD), viscosity, and color characteristics (CIE L*, a*, b*). Increasing ultrasonication time significantly reduced particle size from 177.33 ± 85.55 nm to 19.8 ± 14.89 nm, resulting in a smoother, more homogeneous nanofiber morphology. XRD analysis revealed an amorphous diffraction pattern within the 2? range of 13–25°, indicating the absence of an ordered crystalline structure. The viscosity remained largely stable (9522–9524 mPa·s) between all treatments. Color analysis showed stable L*, a*, and b* values, suggesting that ultrasonication did not induce pigment degradation or noticeable visual changes. These findings demonstrate that prolonged ultrasonication effectively produces uniform, stable, and nano-sized sugar palm flour fibers. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production